1985
DOI: 10.1148/radiology.156.2.3160064
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic falciform artery: anatomy, angiographic appearance, and clinical significance.

Abstract: Three patients developed supraumbilical skin rashes during hepatic artery infusion chemotherapy by a surgically placed perfusion catheter and drug-infusion pump. In one patient, hepatic arterial scintigraphy with technetium-99m macroaggregated serum albumin showed increased uptake corresponding to the rash, and a hepatic arteriogram showed a dilated falciform branch of the left hepatic artery. Surgical ligation of the falciform artery permitted further treatment without recurrent rash. Based on a review of 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
38
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 6 publications
1
38
0
Order By: Relevance
“…In a retrospective study of celiac angiograms performed in 1000 patients, we found an incidence of 18/1000 (unpublished data). Although we have never experienced a supraumbilical skin rash following transcatheter arterial chemotherapy or chemoembolization, and the incidence of this complication is unknown, Williams et al [6] reported that three patients developed supraumbilical skin rashes during hepatic artery infusion chemotherapy through a surgically placed perfusion catheter. In one patient, an hepatic arteriogram showed a dilated falciform branch of the left hepatic artery, and surgical ligation of the falciform artery permitted further treatment without recurrent rash.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…In a retrospective study of celiac angiograms performed in 1000 patients, we found an incidence of 18/1000 (unpublished data). Although we have never experienced a supraumbilical skin rash following transcatheter arterial chemotherapy or chemoembolization, and the incidence of this complication is unknown, Williams et al [6] reported that three patients developed supraumbilical skin rashes during hepatic artery infusion chemotherapy through a surgically placed perfusion catheter. In one patient, an hepatic arteriogram showed a dilated falciform branch of the left hepatic artery, and surgical ligation of the falciform artery permitted further treatment without recurrent rash.…”
Section: Discussionmentioning
confidence: 91%
“…The HFA arises as a terminal branch of the left or middle hepatic artery, runs through the hepatic falciform ligament, distributes itself around the umbilicus, and communicates with branches of the internal thoracic and superior epigastric arteries [6,9,10]. As a small artery, the HFA is observed on angiography only about 2% of the time [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This clinical course is very similar to the skin rash that is rarely noted in the supraumbilical region of the patients who undergo a transcatheter infusion chemotherapy or chemoembolization for hepatocellular carcinoma. In those cases, the hepatic falciform artery has been reported to play an important role [4].…”
Section: Discussionmentioning
confidence: 99%